Improving Mathematics Diagram Learning Outcomes of Grade 2 Students at SDN Cibilik Through the Word Wall Game Assisted by Interactive Flat Panel (IFP) - Faisal Robby Reytama; Siti Solihat (Educational Researcher Journal, 2026)
ABSTRACT This study aims to describe the improvement of mathematics diagram learning outcomes of Grade 2 students at SDN Cibilik through the implementation of the Word Wall game assisted by an Interactive Flat Panel (IFP). The low learning outcomes, with only 25% of students achieving the Minimum Mastery Criterion (MMC) in the pre-cycle condition, serve as the background of this research. The study employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart model, conducted in two cycles. The research subjects were 12 Grade 2 students at SDN Cibilik in the even semester of the 2025/2026 academic year. Data were collected through end-of-cycle written tests and student learning activity observation sheets. The results showed significant improvements in each cycle: the class mean score increased from 60.0 in the pre-cycle to 71.6 in Cycle I and 83.6 in Cycle II. The classical mastery rate rose from 25.0% to 66.7%, and finally reached 100.0% in Cycle II, exceeding the 80% success criterion. These findings confirm the effectiveness of combining Word Wall and IFP in creating active, interactive, and visually engaging learning environments that enhance students' understanding of diagram concepts.